The derivation of denitrification conditions in groundwater: Combined method approach and application for Germany. (November 2022) - Wolters, Tim; Bach, Thomas; Eisele, Michael; Eschenbach, Wolfram; Kunkel, Ralf; McNamara, Ian; Well, Reinhard; Wendland, Frank
Graphical abstract: Highlights: Denitrification conditions in groundwater derived based on redox-sensitive parameters. Inverse distance weighting (IDW) combined with a grid based overlay method. Integration with a reaction kinetics model to quantify denitrification in aquifers. Modeled denitrification show good agreement with results from the N2 /Ar method. Abstract: Denitrification in groundwater is an important process that helps to maintain environmental standards, yet there are very few studies that determine the spatial variation of denitrification conditions in aquifers on a regional scale. We introduce a procedure to derive spatially continuous estimates of denitrification conditions in groundwater based on the interpolation of measurements of the redox-sensitive parameters oxygen, nitrate, iron, manganese and DOC, combined with the quantification of denitrification using a 2D-hydrodynamic model based on first-order reaction kinetics. We applied this procedure to Germany, using measured values from more than 24, 000 groundwater monitoring sites from 2007 to 2016. Annual concentrations of the five parameters at the monitoring sites were regionalized using an optimized, iterative inverse distance weighting procedure within 15 aquifer typologies for spatial delineation. The annual grids (2007–2016) of each parameter were then overlaid and a median over time was calculated. Discrete ranks were then assigned to the concentrations of each parameter based on their redox class, and ultimately, after overlaying the five parameters, a mean value was calculated describing the nitrate degradation conditions in groundwater. After assigning half-life times and reaction constants to those denitrification conditions, we quantified denitrification in groundwater using the hydrodynamic model WEKU. To assess the plausibility of the derived denitrification in groundwater, we compared our results with the proportion of denitrified nitrate determined with the N2 /Ar method at 820 groundwater monitoring wells in three German Federal States, which showed an overall good agreement. Accordingly, the method presented here is suitable to be used for the regionally differentiated derivation of denitrification conditions in groundwater. For regions with denitrifying groundwater conditions, the results provide an explanation for frequently observed discrepancies between high nitrate emissions from the soil and low nitrate concentrations in the groundwater of intensively used agricultural areas.